Classification of profit-sharing investment accounts: A survey of financial statements of Islamic banks in Asia. Issue 3 (21st August 2017) - Suandi, Aprilia Beta
Abstract : Purpose: The purpose of this paper is to examine the classification of profit-sharing investment accounts (PSIAs) under various accounting standards, and determine whether Islamic banks maintain uniform practices when the same accounting standards are applied. It also aims to determine whether Islamic banks consider investment account holders (IAHs) important financial statement users by disclosing necessary information pertaining to PSIAs. Design/methodology/approach: A sample composed of financial statements from 63 Islamic banks from 15 countries is compared with respect to the information related to PSIAs. Findings: The results show heterogeneity of classification for PSIAs. Applying the same standards does not lead to the uniform classification of PSIAs when banks apply International Financial Reporting Standards, while financial statements applying Financial Accounting Standards by the Accounting and Auditing Organization for Islamic Financial Institutions are more similar. The perplexity in classifying PSIAs brings obscurity on the treatment for PSIA-related accounts, particularly returns attributable to IAHs. The fact of fewer disclosures pertaining to PSIAs in Islamic banks – which apply accounting standards not specifically tailored to Islamic finance – suggests that IAHs receive less attention under those accounting standards. Research limitations/implications: The main limitation relates to the lack of financial statements available online and the possibility of sample selection bias toward larger Islamic banks. Originality/value: This research contributes to the limited literature on accounting for PSIAs, and reveals the diversity of reporting methods for unique transactions in Islamic banks and the insufficiency of current accounting standards to guide them, which create possible challenges of comparability.